ADVENTURE TOURISM IN UZBEKISTAN - Nazarova Malika (TADQIQOTLAR, 2025)
This research provides a comprehensive analysis of the development, challenges, and prospects of adventure tourism in Uzbekistan. The study investigates the country’s natural landscapes, government initiatives, and international interest in outdoor and cultural experiences. Data from national tourism agencies, global reports, and stakeholder interviews are utilized to highlight current trends and identify areas for growth. Findings indicate that Uzbekistan holds strong potential for becoming a leading adventure tourism destination in Central Asia due to its unique geographical diversity and cultural richness. However, infrastructure improvement, safety regulations, and sustainable tourism practices remain essential for sector development.These findings contribute to the understanding of sustainable development in emerging adventure destinations and provide actionable insights for tourism stakeholders.